A Social Identity Analysis of Climate Change and Environmental Attitudes and Behaviors: Insights and Opportunities - Fielding, Kelly S.; Hornsey, Matthew J. (Frontiers in Psychology, 2016)
Environmental challenges are often marked by an intergroup dimension. Political conservatives and progressives are divided on their beliefs about climate change, farmers come into conflict with scientists and environmentalists over water allocation or species protection, and communities oppose big business and mining companies that threaten their local environment. These intergroup tensions are reminders of the powerful influence social contexts and group memberships can have on attitudes, beliefs, and actions relating to climate change and the environment more broadly. In this paper we use social identity theory to help describe and explain these processes. We review literature showing how conceiving of oneself in terms of a particular social identity influences our environmental attitudes and behaviors, how relations between groups can impact on environmental outcomes, and how the content of social identities can direct group members to act in more or less pro-environmental ways. We discuss the similarities and differences between the social identity approach to these phenomena and related theories such as cultural cognition theory, the theory of planned behavior and value-belief-norm theory. Importantly, we also advance social-identity based strategies to foster more sustainable environmental attitudes and behaviors. Although this theoretical approach can provide important insights and potential solutions, more research is needed to build the empirical base, especially in relation to testing social identity solutions.